2006
DOI: 10.1016/j.icesjms.2005.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of diamond- and square-mesh codends in the deepwater crustacean trawl fishery off the Balearic Islands (western Mediterranean)

Abstract: An analysis of 38 bottom trawl hauls at depths of 251–737 m off the Balearic Islands (western Mediterranean) during autumn 2002 and spring 2003 was used to compare the species and size selectivity of 40-mm diamond- and square-mesh codends under commercial conditions. There was no difference in the catch composition or the yield that could be attributable to mesh shape, although the percentage of total and commercial species discarded with a diamond mesh was higher than with a square mesh. At least in the short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
100
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(119 citation statements)
references
References 26 publications
16
100
3
Order By: Relevance
“…Our L 50 estimated for hake with the 20-mm sorting grid (ca 13.3 cm) is close to that (14.2 cm) estimated earlier by Sardà et al (2005) with a similar 20-mm grid. However, our estimates of selection range (3.1 and 2.4 cm) are substantially smaller than theirs (7.3 cm), suggesting that small changes in rigging of the grid may cause major changes in SR. Our selectivity parameters for hake with the 40-mm square mesh (L 50 =18.5 cm, SR= 5.1 cm) were higher than those reported in the Balearic Islands (L 50 = 15.4 cm, SR = 4.5) (Guijarro and Massuti, 2006), probably due to the use in the islands of a thinner knotted PA netting operating in deepwater (>500 m) and at a lower speed (2.5 knots). The 20-mm sorting grid also came out as an effective selection device for red mullet.…”
Section: Mullus Barbatuscontrasting
confidence: 73%
“…Our L 50 estimated for hake with the 20-mm sorting grid (ca 13.3 cm) is close to that (14.2 cm) estimated earlier by Sardà et al (2005) with a similar 20-mm grid. However, our estimates of selection range (3.1 and 2.4 cm) are substantially smaller than theirs (7.3 cm), suggesting that small changes in rigging of the grid may cause major changes in SR. Our selectivity parameters for hake with the 40-mm square mesh (L 50 =18.5 cm, SR= 5.1 cm) were higher than those reported in the Balearic Islands (L 50 = 15.4 cm, SR = 4.5) (Guijarro and Massuti, 2006), probably due to the use in the islands of a thinner knotted PA netting operating in deepwater (>500 m) and at a lower speed (2.5 knots). The 20-mm sorting grid also came out as an effective selection device for red mullet.…”
Section: Mullus Barbatuscontrasting
confidence: 73%
“…We accounted only for VMS signals from bottom trawlers, as these species are mainly caught with this type of gear in the study area. Only signals with speed between 1.5 and 5.0 knots were included, which correctly identify fishing activity (e.g., Guijarro and Massutí 2006). In order to account for the effect of fishing effort intensity on body condition, we averaged the sum of signals for each haul within a 3 km radius circle.…”
Section: Fishing Impactmentioning
confidence: 99%
“…Therefore, many researchers have suggested increasing the mesh size and/or changing the mesh shape in the codend. Many studies outside the aegean sea have shown that an increase in mesh size and a change of mesh shape in the trawl codends reduce the number of juvenile P. longirostris caught (sobrino et al, 2000;guijarro and Massutí, 2006;Rinelli et al, 2005;Ragonese and bianchini, 2006). in addition, the general Fisheries Commission for the Mediterranean (gFCM) has encouraged studies aimed at improving selectivity and reducing the discards of this fleet (gFCM 2007).…”
mentioning
confidence: 99%